Preparation method of conductive ink for preparing high-robustness glucose sensor

By introducing carboxylated nanocellulose into the conductive ink to increase the carboxyl content on the electrode surface, the problem of unstable interface between the enzyme and the electrode is solved, and a highly robust glucose sensor is realized, which is suitable for repeated and intermittent use over many days, and High sensitivity and reliability are maintained.

CN119350924APending Publication Date: 2025-01-24SOUTH CHINA UNIV OF TECH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411166077.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing glucose sensors are difficult to maintain stable detection performance when used repeatedly and intermittently, especially when the relationship between the enzyme and the electrode interface is unstable, resulting in low specificity and difficult detection accuracy.

Method used

By introducing carboxyl -based nano -cellulose in the conductive ink as the additive, the carboxyl content of the electrode surface is improved, the enzyme is stable and fixed, and the glucose sensor that is savory is prepared.

Benefits of technology

It achieves a high-performance glucose sensor that can be used repeatedly and intermittently over multiple days, maintains high sensitivity and reliability, and is suitable for complex detection environments and mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350924A_ABST
    Figure CN119350924A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electrochemical biosensors, and discloses a preparation method of conductive ink for preparing a high-robustness glucose sensor, and the preparation method comprises three steps of color paste pre-dispersion, ink mixing and ink grinding. According to the method, carboxylated nanocellulose is introduced into conductive ink to serve as an ink auxiliary agent, so that the carboxyl content of the surface of a screen-printed electrode is remarkably increased; the prepared conductive ink provides a large number of stable enzyme immobilization sites in the modification process of glucose oxidase, the robustness and stability of a glucose sensor in the repeated and intermittent use process are remarkably improved, and the method is simple, efficient and easy to implement. The method is suitable for large-scale production of stable and reliable sweat glucose detection sensors, and has important medical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a biosensor, and in particular to the field of electrochemical biosensors. Background Art

[0002] As the number of patients with diabetes continues to increase, glucose detection technology has become increasingly important in clinical diagnosis and personal health monitoring. Electrochemical methods have become the mainstream method for glucose detection due to their mature technology, ease of use, high cost performance, and suitability for miniaturization. In particular, electrochemical glucose sensors have been widely used in point-of-care testing devices. Among them, screen-printed electrodes (SPE) have become the main method for constructing electrochemical glucose sensors due to their simple preparation and ease of large-scale production.

[0003] Currently, the common POCT glucose sensors on the market are mainly divided into two categories: blood glucose meters and continuous glucose monitoring systems (CGM). Blood glucose meters use disposable blood glucose test strips for detection and cannot be reused multiple times. The CGM system can achieve long-term, uninterrupted continuous monitoring, and its typical working time can reach two weeks. These two sensors each meet different clinical needs, but also expose some limitations in use.

[0004] Between these two types of sensors, there is a blank market that has not yet been fully filled, that is, a glucose sensor that can be used repeatedly and intermittently over multiple days. This sensor requires high robustness to ensure stable detection performance during intermittent use. Traditionally, the preparation method of enzyme-free glucose sensors based on metal alloys or catalysts can partially meet this demand, but due to its low specificity for glucose, it is difficult to achieve accurate detection in complex samples (such as body fluids). Therefore, enzyme-based glucose sensors have become a more attractive option, especially in detections that require high specificity.

[0005] Although enzymatic glucose sensors have significant advantages in specificity, they also face some challenges in practical applications, especially when building sensors that can be used repeatedly and intermittently. The complex interaction between the enzyme and the electrode makes it difficult to maintain a stable enzyme-electrode interface relationship under intermittent use, which is why the current CGM system can only achieve continuous monitoring. Therefore, how to achieve a steady-state enzyme-electrode interface relationship on the electrode surface has become the key to the development of glucose sensors that can be used repeatedly and intermittently.

[0006] In glucose sensors built on screen-printed electrodes, the preparation of conductive inks is crucial. Existing conductive inks are usually doped with only electron mediators for detection purposes (such as Prussian blue, ferrocene and its derivatives), but these inks still have deficiencies in the long-term stability and robustness of sensors. In particular, facing the needs of repeated and intermittent use, existing technologies are difficult to meet the requirements.

[0007] The present invention proposes a new method for preparing conductive ink. Unlike the traditional method, in addition to adding an electron mediator, carboxylated nanocellulose is also introduced as an ink additive. This innovative combination aims to improve the robustness of the conductive ink, thereby preparing a high-performance glucose sensor that can be used repeatedly and intermittently over multiple days. Summary of the invention

[0008] The present invention aims to solve the problem of unstable steady-state relationship between enzyme and electrode interface in the prior art, and provides a novel method for preparing conductive ink. By incorporating carboxylated nanocellulose (CNF) as an additive into the conductive ink containing an electron mediator, the carboxyl content on the surface of the SPE electrode is greatly increased, and a highly robust enzyme fixation effect is achieved, thereby preparing a stable and reliable sweat glucose detection sensor.

[0009] The specific technical solutions are as follows

[0010] A method for preparing a conductive ink for preparing a highly robust glucose sensor, characterized in that the conductive ink comprises the following components: a conductive filler, an electron mediator, a resin connecting material, a solvent, an auxiliary agent, and carboxylated nanocellulose, and the preparation method comprises the following steps:

[0011] S1. Pre-dispersion of color paste: Mix the resin binder, solvent, additive and carboxylated nanocellulose in a mixing drum to pre-disperse the color paste;

[0012] S2. Ink mixing: Under stirring conditions, the pre-dispersed color paste is mixed with a conductive filler, an electronic mediator and a curing agent to mix the ink;

[0013] S3. Ink grinding: Grind the conductive ink pre-dispersion to a desired fineness to obtain the conductive ink.

[0014] In some embodiments, the conductive filler is selected from one or more of graphite, carbon powder, graphene, carbon nanotubes, fullerenes, functionalized graphene, functionalized carbon nanotubes, gold powder and platinum powder.

[0015] In some embodiments, the electron mediator is selected from one or more of Prussian blue, ferrocene and their derivatives.

[0016] In some embodiments, the resin binder is selected from one or more of methyl phenyl silicone resin, epoxy resin, carboxymethyl cellulose, cellulose acetate and bisphenol-formaldehyde resin.

[0017] In some embodiments, the auxiliary agent includes a leveling agent, a defoaming agent and a thickener.

[0018] In some embodiments, the leveling agent includes one or more of polyethylene glycol, polyvinyl pyrrolidone, and polyvinyl alcohol.

[0019] In some embodiments, the defoaming agent is one or more of Tween-20, Triton-100, sodium dodecyl sulfate, dodecylpyridinium chloride, hexadecylpyridinium bromide, hexadecyltrimethylammonium bromide, and tributyl phosphate.

[0020] In some embodiments, the color paste pre-dispersion step is carried out by stirring at a rotation speed of 1500-1600 r / min for 15-25 minutes.

[0021] In some embodiments, the ink mixing step is performed by stirring at a rotation speed of 3000-3200 r / min for 25-35 minutes.

[0022] In some embodiments, the grinding step is performed by a three-roll mill, and the number of grinding times is 4-6 times.

[0023] The present invention has the following advantages

[0024] (1) The present invention introduces carboxylated nanocellulose into the conductive ink, so that the electrode surface prepared has a high abundance of carboxyl content, which greatly improves the stability of enzyme fixation.

[0025] (2) The conductive ink can be printed into a highly robust glucose sensor suitable for repeated and intermittent use.

[0026] (3) The glucose sensor prepared using this ink still has high sensitivity and reliability under complex detection environments and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The rheological properties of the conductive ink after changing the CNF addition ratio in Example 6, Figure a shows the relationship between the shear rate and viscosity of the ink, and Figure b shows the relationship between the shear rate and stress of the ink.

[0028] Figure 2 This is the adhesion test of the conductive ink after changing the CNF addition ratio in Example 6. Figures a to d are the adhesion tests of the conductive ink with CNF added in 0.1%, 0.5%, 1%, and 1.5% mass ratios, respectively.

[0029] Figure 3 The continuous electrochemical response of the SPE electrode printed with the conductive ink of CNF in Example 6 to hydrogen peroxide in the absence of enzyme within 15 days (Figure a), and the continuous electrochemical response of the electrode to glucose after glucose oxidase was immobilized (Figure b).

[0030] Figure 4 The electrochemical response stability of the SPE electrode printed with the conductive ink containing CNF in Example 6 to glucose within 15 days after glucose oxidase was fixed. DETAILED DESCRIPTION

[0031] In order to facilitate the understanding of the technical implementation method of the present invention, the technical scheme in the embodiment of the present invention will be clearly and completely described below in combination with the technical process steps, specific implementation conditions and materials in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1

[0033] Conductive ink preparation

[0034] (1) Pre-dispersion of color paste: 15 parts of methylphenyl silicone resin, 15 parts of cellulose acetate, 15 parts of ethanol, and 25 parts of acetone were mixed evenly, and then 0.5 parts of butyl titanate, 0.5 parts of tributyl phosphate, 3 parts of dispersant BYK-W966, and 0.2 parts of polyethylene glycol were added. The mixture was stirred at 1500 r / min in a high-speed disperser for 15 minutes. Finally, an ethanol dispersion containing carboxylated nanocellulose was added to make the final proportion of carboxylated nanocellulose 0.5%.

[0035] (2) Ink mixing: 15 parts of conductive carbon black, 2 parts of multi-walled carbon nanotubes, and 2 parts of Prussian blue were added to mixture A, and stirred at 3000 r / min in a high-speed disperser for 30 minutes. 1 part of curing agent N,N-dimethylbenzylamine was added and stirring was continued for 5 minutes to obtain a conductive ink predispersion B.

[0036] (3) Ink grinding: The pre-dispersion B was ground five times on a three-roll mill to prepare a conductive ink.

[0037] Example 2

[0038] Conductive ink preparation

[0039] (1) Pre-dispersion of color paste: 17 parts of cellulose acetate, 23 parts of bisphenol-formaldehyde resin, 23 parts of ethanol, and 17 parts of acetone were mixed evenly, and then 0.7 parts of butyl titanate, 0.6 parts of tributyl phosphate, 4 parts of dispersant BYK-W966, and 0.2 parts of polyethylene glycol were added. The mixture was stirred at 1500 r / min in a high-speed disperser for 20 minutes, and finally, an ethanol dispersion containing carboxylated nanocellulose was added to make the final proportion of carboxylated nanocellulose 1.0%.

[0040] (2) Ink mixing: 16 parts of conductive carbon black, 1 part of multi-walled carbon nanotubes, 2 parts of fullerenes, and 2 parts of Prussian blue were added to mixture A, and stirred at 3100 r / min in a high-speed disperser for 28 minutes. 1 part of curing agent N,N-dimethylbenzylamine was added and stirring was continued for 5 minutes to obtain a conductive ink predispersion B.

[0041] (3) Ink grinding: The pre-dispersion B was ground five times on a three-roll mill to prepare a conductive ink.

[0042] Example 3

[0043] Conductive ink preparation

[0044] (1) Pre-dispersion of color paste: 15 parts of bisphenol epoxy resin, 20 parts of bisphenol novolac resin, 15 parts of ethanol, and 25 parts of acetone were mixed evenly, and then 0.5 parts of butyl titanate, 0.5 parts of tributyl phosphate, 3 parts of dispersant BYK-W966, and 0.2 parts of polyethylene glycol were added. The mixture was stirred at 1550 r / min in a high-speed disperser for 17 minutes, and finally an ethanol dispersion containing carboxylated nanocellulose was added to make the final proportion of carboxylated nanocellulose 1.5%.

[0045] (2) Ink mixing: 13 parts of carbon powder, 3 parts of multi-walled carbon nanotubes, 3 parts of gold powder, and 2 parts of Prussian blue were added to mixture A, and stirred at 3100 r / min for 33 minutes in a high-speed disperser. 1 part of curing agent N,N-dimethylbenzylamine was added and stirring was continued for 5 minutes to obtain a conductive ink pre-dispersion B.

[0046] (3) Ink grinding: The pre-dispersion B was ground five times on a three-roll mill to prepare a conductive ink.

[0047] Example 4

[0048] Conductive ink preparation

[0049] (1) Pre-dispersion of color paste: 18 parts of bisphenol epoxy resin, 18 parts of bisphenol novolac resin, 15 parts of ethanol, and 25 parts of acetone were mixed evenly, and then 0.5 parts of butyl titanate, 0.5 parts of tributyl phosphate, 3 parts of dispersant BYK-W966, and 0.2 parts of polyethylene glycol were added. The mixture was stirred at 1560 r / min in a high-speed disperser for 18 minutes. Finally, an ethanol dispersion containing carboxylated nanocellulose was added to make the final proportion of carboxylated nanocellulose 3%.

[0050] (2) Ink mixing: 10 parts of functionalized carbon nanotubes, 3 parts of carbon powder, 3 parts of platinum powder, and 2 parts of ferrocene were added to mixture A, and stirred at 3050 r / min for 33 minutes in a high-speed disperser. 1 part of curing agent N,N-dimethylbenzylamine was added and stirring was continued for 5 minutes to obtain a conductive ink predispersion B.

[0051] (3) Ink grinding: The pre-dispersion B was ground six times on a three-roll mill to prepare a conductive ink.

[0052] Example 5

[0053] Conductive ink preparation

[0054] (1) Pre-dispersion of color paste: 13 parts of bisphenol epoxy resin, 18 parts of cellulose acetate, 15 parts of ethanol, and 25 parts of methylphenyl silicone resin were mixed evenly, and then 0.5 parts of butyl titanate, 0.5 parts of tributyl phosphate, 3 parts of dispersant BYK-W966, and 0.2 parts of polyethylene glycol were added. The mixture was stirred at 1600 r / min in a high-speed disperser for 19 minutes, and finally an ethanol dispersion containing carboxylated nanocellulose was added to make the final proportion of carboxylated nanocellulose 1%.

[0055] (2) Ink mixing: Add 2 parts of conductive carbon black, 15 parts of multi-walled carbon nanotubes, and 3 parts of Prussian blue to mixture A, stir at 3200 r / min in a high-speed disperser for 20 minutes, add 1 part of curing agent N,N-dimethylbenzylamine and continue stirring for 6 minutes to obtain a conductive ink predispersion B.

[0056] (3) Ink grinding: The pre-dispersion B was ground five times on a three-roll mill to prepare a conductive ink.

[0057] Example 6

[0058] Conductive ink preparation and performance testing

[0059] (1) Pre-dispersion of color paste: 15 parts of bisphenol epoxy resin, 20 parts of bisphenol novolac resin, 15 parts of ethanol, and 25 parts of acetone were mixed in a mixing drum, and then 0.5 parts of coupling agent butyl titanate, 0.5 parts of defoaming agent tributyl phosphate, 3 parts of dispersant BYK-W966, and 0.2 parts of active agent polyethylene glycol were added in a high-speed disperser and stirred at 1500r / min for 15 minutes. Finally, an ethanol dispersion containing CNF was added thereto so that the final CNF accounted for 0.1% of the total ink mass ratio to obtain a mixture A.

[0060] (2) Ink mixing: 16 parts of conductive carbon black, 1 part of multi-walled carbon nanotubes, and 2 parts of Prussian blue were added to mixture A under stirring, and the mixture was stirred at 3000 r / min in a high-speed disperser for 30 minutes. Then, 1 part of curing agent N,N-dimethylbenzylamine was added and stirring was continued for 5 minutes to obtain a conductive ink predispersion B.

[0061] (3) Ink grinding: The conductive ink pre-dispersion B is ground five times on a three-roller grinder to achieve the desired fineness, thereby obtaining the conductive ink.

[0062] According to the ink formula shown in Table 1, five types of conductive inks, No. 1 to No. 5, were prepared according to different amounts of CNF added.

[0063] Table 1. Conductive ink formulas at different CNF doping ratios

[0064]

[0065]

[0066] Rheological properties of five conductive inks are shown in Figure 2. Figure 1 As shown. Figure 1 It can be seen that the prepared ink has obvious non-Newtonian fluid behavior. When the shear rate increases, the ink shows shear thinning behavior because the increasing shear rate destroys the structure of the ink. The rate of decline of the curve represents the ease with which the ink system is destroyed. The coagulated structure formed by the 2% mass fraction of ink pigment particles is most easily destroyed. In addition, from Figure 1 It can be seen from Figure b that as the shear rate increases, the shear stress curve trend of the ink containing 1.5% and 2% mass fraction CNF changes greatly, and finally even becomes a straight line approximately parallel to the horizontal axis. This shows that as the amount of CNF added increases, when the shear rate gradually increases, the movement of the pigment particles in the ink with 2% mass fraction CNF added has a consistent and greatest obstacle under the action of external force. This phenomenon will cause the pigment particles to flocculate and reduce the fluidity of the ink, making it increasingly difficult to apply ink to the screen, and even causing ink blocking. Therefore, in the subsequent ink-related tests, four other inks were used.

[0067] The adhesion test results of the other four inks are as follows: Figure 2 The adhesion test is carried out in accordance with GB9286-88 Cross-cut test for paint and varnish films. Figure 2 It can be seen that when the added CNF is 1.5% by mass, there is partial and large flakes along the edge of the cut, and some of the grids are almost completely peeled off, indicating that the ink fails the 100-grid test. After the 100-grid test, the edges of the cuts of the other three inks are completely smooth and there is no peeling at the edges of the grids, and they pass the 100-grid test.

[0068] The resistivity of the three inks was tested, and the resistivity test was carried out using the four-probe method. As can be seen from Table 2, as the mass fraction of CNF added increases, the resistivity of the ink also gradually increases. This is because CNF has poor conductivity and relatively small size. When its content in the conductive ink increases, it will destroy the mutual contact between the conductive pigments and reduce the tunnel current. However, in electrochemical analysis, the chemical reaction occurring at the electrode / electrolyte interface is important. The increase in the movement barrier (resistivity) of the homogeneous electrons at the base electrode does not have a great effect on the electrode indicating heterogeneous electron transfer. Therefore, in order to obtain the maximum electrode surface carboxyl content to increase the amount of GOx fixed, thereby increasing the content of enzymatic reaction products on the electrode surface per unit time, so as to increase the number of heterogeneous electron transfers, thereby improving the current sensitivity of the electroanalysis response; a conductive ink with a CNF doping mass fraction of 1% was selected as the working electrode printing ink for the preparation of the glucose sensor.

[0069] Table 2. Resistivity test of conductive ink at different CNF doping ratios

[0070]

[0071] The prepared electrode was subjected to electrochemical testing. The solution conditions for the electrochemical test were carried out in artificial sweat, which contained 85.56mmol / L NaCl, 14.10mmol / L NaH2PO4 and 2.385mmol / L L-histidine, and the final pH value of the artificial sweat was 5.5. The electrochemical method conditions were: it method, operating voltage was -0.2V (relative to the Ag / AgCl reference electrode). The solution was stirred during the test, and the speed was constant.

[0072] like Figure 3 As shown in Figure a, it can be seen that the SPPE@CNF electrode has a relatively stable electrochemical response to hydrogen peroxide within 15 days, and the curve fluctuation at high concentration is caused by the matrix effect of artificial sweat. This shows that the electrode made of conductive ink has a stable electrochemical response to hydrogen peroxide. On this basis, the same electrochemical characterization was performed on the enzyme electrode's ability to be reused for 15 days. Figure 3 As can be seen in Figure b, after glucose oxidase (GOx) was modified on the electrode surface, the SPPE@CNF-GOx electrode showed very good continuous detection stability for glucose within 15 days. This stability is brought about by the conductive ink added with carboxylated nanocellulose. In this paper, carboxylated nanocellulose is mixed into the ink through an ink mixing method to provide a large number of firm carboxylated fixation sites for the fixation of GOx, so that the enzyme electrode has very good reusability within 15 days. At the same time, the use of conductive ink modified with carboxylated nanocellulose also ensures that the glucose sensor prepared by screen printing has stable intra-batch differences, and the results are shown in Figure 2. Figure 4 shown.

[0073] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a conductive ink for preparing a highly robust glucose sensor, characterized in that: The conductive ink comprises the following components: conductive filler, electronic mediator, resin connecting material, solvent, auxiliary agent, carboxylated nanocellulose, and the preparation method comprises the following steps: S1. Pre-dispersion of color paste: Mix the resin binder, solvent, additive and carboxylated nanocellulose in a mixing drum to pre-disperse the color paste; S2. Ink mixing: Under stirring conditions, the pre-dispersed color paste is mixed with a conductive filler, an electronic mediator and a curing agent to mix the ink; S3. Ink grinding: Grind the conductive ink pre-dispersion to achieve the required fineness to obtain the conductive ink.

2. The method for preparing a conductive ink for preparing a highly robust glucose sensor according to claim 1, characterized in that: The conductive filler is selected from one or more of graphite, carbon powder, graphene, carbon nanotubes, fullerene, functionalized graphene, functionalized carbon nanotubes, gold powder and platinum powder.

3. The method for preparing a conductive ink for preparing a highly robust glucose sensor according to claim 1, characterized in that: The electron mediator is selected from one or more of Prussian blue, ferrocene and their derivatives.

4. The method for preparing a conductive ink for preparing a highly robust glucose sensor according to claim 1, characterized in that: The resin binder is selected from one or more of methyl phenyl silicone resin, epoxy resin, carboxymethyl cellulose, cellulose acetate and bisphenol-formaldehyde resin.

5. The method for preparing a conductive ink for preparing a highly robust glucose sensor according to claim 1, characterized in that: The auxiliary agents include leveling agents, defoaming agents and thickeners.

6. The method for preparing a conductive ink for preparing a highly robust glucose sensor according to claim 5, characterized in that: The leveling agent includes one or more of polyethylene glycol, polyvinyl pyrrolidone and polyvinyl alcohol.

7. The method for preparing a conductive ink for preparing a highly robust glucose sensor according to claim 5, characterized in that: The defoaming agent is one or more of Tween-20, Triton-100, sodium dodecyl sulfate, dodecylpyridinium chloride, hexadecylpyridinium bromide, hexadecyltrimethylammonium bromide and tributyl phosphate.

8. The method for preparing a conductive ink for preparing a highly robust glucose sensor according to claim 1, characterized in that: The color paste pre-dispersion step is carried out by stirring at a rotation speed of 1500-1600 r / min for 15-25 minutes.

9. The method for preparing a conductive ink for preparing a highly robust glucose sensor according to claim 1, characterized in that: The ink mixing step is performed by stirring at a rotation speed of 3000-3200 r / min for 25-35 minutes.

10. The method for preparing a conductive ink for preparing a highly robust glucose sensor according to claim 1, characterized in that: The grinding step is performed by a three-roll mill, and the number of grinding times is 4-6 times.

Citation Information

Patent Citations

  • Glucose oxidase screen-printed electrode for online detection and preparation method thereof

    CN107238645A

  • Preparation of glucose sensor based on graphene and graphene oxide composite material

    CN107436316A

  • Glucose biosensor, glucose sensing film thereof and glucose dehydrogenase

    CN113717955A

  • Construction method of glucose biosensor assembled based on glutathione

    CN113758983A

  • High-conductivity water-based graphene ink and preparation method thereof

    CN114276713A